Current Trends and Research Hotspots in Pancreatic Stellate Cells: A Bibliometric Study - Yang, Zhaoming; Xie, Zhiqin; Wan, Jian; Yi, Bo; Xu, Tao; Shu, Xiaorong; Zhao, Zhijian; Tang, Caixi (Frontiers in Oncology, 2022)
Background: Pancreatic stellate cells (PSCs) play crucial roles in acute/chronic pancreatitis and pancreatic cancer. In this study, bibliometric analysis was used to quantitatively and qualitatively analyze the literature related to PSCs from 1998-2021 to summarize the current trends and research topics in this field. Methods: Relevant literature data were downloaded from the Science Citation Index Expanded Web of Science Core Collection (WoSCC) on April 07, 2021, using Clarivate Analytics. Biblioshiny R packages, VOSviewer, Citespace, BICOMB, gCLUTO, and the Online Analysis Platform of Literature Metrology (http://bibliometric.com) were used to analyze the manually selected data. Results: A total of 958 relevant studies published in 48 countries or regions were identified. The United States of America (USA) had the highest number of publications, followed by the People’s Republic of China, Germany, and Japan. Tohoku University (Japan), the University of New South Wales (Australia), the University of Texas MD Anderson Cancer Center (USA), Technical University of Munich (Germany), and University of Rostock (Germany) were the top five institutions with most publications. Nine major clusters were generated using reference co-citation analysis. Keyword burst detection revealed that progression (2016-2021), microenvironment (2016-2021), and tumor microenvironment (2017-2021) were the current frontier keywords. Biclustering analysis identified five research hotspots in the field of PSCs during 1998-2021. Conclusion: In this study, a scientometric analysis of 958 original documents related to PSCs showed that the research topics of these studies are likely in the transition from acute/chronic pancreatitis to pancreatic cancer. The current research trends regarding PSCs are related to pancreatic cancer, such as tumor microenvironment. This study summarizes five research hotspots in the field of PSCs between 1998 and 2021 and thus may provide insights for future research. Keywords: pancreatic stellate cells, acute/chronic pancreatitis, pancreatic cancer, bibliometric analysis, research hotspots